Nature vs. Nurture: Clinical and Cephalometric Pattern in Twins - Jeenal K. Gupta; Vijayendra K. Jain; Kailash Chandra Gupta; Kunal K. Gupta (Research Highlights in Disease and Health Research Vol. 8, 2023)
The aim of this study of monozygotic twins is to assess the genetic and environmental components of variation within the cranio-dento-facial complex. Malocclusion is a developmental problem inducing a deviation from the normal or ideal occlusion. It’s known to be the manifestation of the genetic and environmental interaction on craniofacial development. Genetic factors are thought to predominate during embryonic craniofacial morphogenesis, while environmental factors are said to have a postnatal influence on dentofacial morphology, particularly during the growth period. Orthodontists usually assume that genetic factors are of major significance to the development of malocclusion. Studies of twin similarities have lent support to this concept. Twin studies is one of the common method to study the role of genes. The twin method provides geneticists with one of the most informative techniques available for analysis of complex genetic traits. The study of craniofacial relationship in twins has provided much useful information concerning the role of malocclusion. Studies of twin similarities have lent support to this concept. Twin studies are one of the most effective methods for investigating genetically determined malocclusion variables. Discordancy is a common occurrence in dizygotic twins. Discordancy in monozygotic twins, on the other hand, is a rare occurrence. Environmental factors do play an important role in the discordance of malocclusion in twins. By studying twins, researchers can understand about the role of genetic effects and the effects of shared and unique environment effects.